Phenotypic variability in male patients carrying the mutant ornithine transcarbamylase (OTC) allele, Arg40His, ranging from a child with an unfavourable prognosis to an asymptomatic older adult. Issue 8 (August 1996) - Matsuda, I; Matsuura, T; Nishiyori, A; Komaki, S; Hoshide, R; Matsumoto, T; Funakoshi, M; Kiwaki, K; Endo, F; Hata, A; Shimadzu, M; Yoshino, M
Abstract : In five different Japanese families, we identified six male hemizygotes (aged 6, 9, 15, 17, 56, and 65 years) and a putative candidate (aged 48 years), carrying a mutant allele of the ornithine transcarbamylase (OTC) gene, a G to A substitution at nucleotide 119 in exon 2 generating histidine in place of arginine. OTC activity in the necropsied liver tissue was reduced to approximately 12% of the control and that of COS 1 cells transfected with Arg40His OTC cDNA was 10.2 +/- 1.8% of the control transfected with wild type OTC cDNA. Clinical features ranged from death during a hyperammonaemic attack (a 9 year old) to a 65 year old asymptomatic man. We consider that the amount of protein ingested by these subjects may be one predisposing factor leading to the manifestation of this disease.